2017
DOI: 10.1139/apnm-2016-0410
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference is associated with liver fat in black and white adolescents

Abstract: Abstract:We examined whether waist circumference (WC) is associated with liver fat in black and white adolescents. Liver fat was measured using a 3T proton magnetic resonance spectroscopy ( 1 H-MRS) in 152 overweight/obese adolescents (94 black and 58 white, body mass index (BMI) ≥85th percentile, aged 12-18 years) without liver diseases or diabetes. WC was measured at the last rib. Total and visceral adipose tissue (VAT) were measured by dual-energy X-ray absorptiometry and magnetic resonance imaging, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…An interesting report from Mexico found that maternal weight status might be related to fatty liver content in their children as young adults after controlling for their own BMI 40 . Our findings do not agree with a report showing that waist circumference, a measure of abdominal adiposity, was a stronger predictor of liver fat than BMI among a study of adolescents 41 …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…An interesting report from Mexico found that maternal weight status might be related to fatty liver content in their children as young adults after controlling for their own BMI 40 . Our findings do not agree with a report showing that waist circumference, a measure of abdominal adiposity, was a stronger predictor of liver fat than BMI among a study of adolescents 41 …”
Section: Discussioncontrasting
confidence: 99%
“…The current investigation has several strengths, foremost the MRI‐based measurement of liver fat in a substantial sample size of generally healthy children and adolescents. Previous population surveys classified children and adolescents according to ALT concentrations, 2,6 whereas MRI‐based investigations focused on children with overweight/obesity 15,39,41,42 . The wide age range, the ethnic diversity, and the substantial proportion of participants with overweight and obesity included by design make these findings applicable to a more general population.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies selected here it is observed that different methods were used to identify hepatic steatosis: liver biopsy[ 9 ], computed tomography[ 14 ], proton magnetic resonance spectroscopy[ 8 , 15 ] being that the great majority realized abdominal ultrasonography[ 10 , 11 , 16 - 20 ].…”
Section: Clinical Anthropometric Indicators Of Visceral Adipositymentioning
confidence: 99%
“…In children, the WC AUC was 0.94, with the cutoff point at the 80th percentile for age, in the study by Zhang et al[ 17 ], a cross sectional study with 7229 students in China. Lee et al[ 15 ] evaluated white and black obese adolescents in the United States and found an optimal WC cutoff point for predicting NAFLD of 101.5 cm, AUC: 0.847, 93% sensitivity and 80% specificity in white obese women, and with no statistical difference between the values found between the blacks. The cross-sectional study by Monteiro et al[ 16 ], which evaluated 145 obese children and adolescents in Brazil, found higher WC (AUC: 0.720) when compared to trunk fat mass (AUC: 0.661), estimated by Dual-energy X-ray absorptiometry, however lower than the intra-abdominal adipose tissue (AUC: 0.741), measured by ultrasound examination.…”
Section: Waist Circumferencementioning
confidence: 99%
“…The unequal prevalence of the disease in representatives of different ethnic groups and the different rates of its progression in individuals with the same or similar risk factors and environmental conditions indicate the pathogenetic role of hereditary factors [12,13].…”
mentioning
confidence: 99%